Digitalisasi Pengelolaan Keuangan Desa: Analisis Implementasi Aplikasi Keuangan pada BUMDes Bebedahan Berkah - Anisa Anisa; Asih Handayani; Khanif Faozi (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to analyze the implementation of financial applications in improving the efficiency, transparency, and accountability of financial management of Village-Owned Enterprises (BUMDes) Bebedah Berkah. Before the implementation of the application, BUMDes faced obstacles in the form of manual recording, limited human resources, and low accountability of financial statements. The research uses a qualitative approach with phenomenological methods to understand the manager's experience in using the TAKABUMDes application. Data was obtained through in-depth interviews, observations, and documentation, then analyzed descriptively through data reduction, data presentation, and conclusion drawn. The results of the study show that the TAKABUMDes application improves the financial recording and reporting system to be more systematic, timely, and in accordance with the Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP). This application also supports the application of good governance principles, especially transparency, accountability, and community participation, as well as increasing public trust in the management of BUMDes. This study recommends strengthening human resource capacity, optimizing information technology, and participatory supervision systems to realize modern and sustainable BUMDes. This research involved eight key informants consisting of the Chairman, Treasurer, Secretary, as well as community representatives and village officials. Empirical results show that the efficiency of financial recording is increased by up to 40% faster than manual systems, and the preparation of financial statements is now carried out regularly every month.